The health consequences of child marriage: a systematic review of the evidence - Suiqiong Fan; Alissa Koski (BMC, 2022)
Abstract Background Child marriage, defined as marriage before 18 years of age, is a violation of human rights and a marker of gender inequality. Growing attention to this issue on the global development agenda also reflects concerns that it may negatively impact health. We conducted a systematic review to synthesize existing research on the consequences of child marriage on health and to assess the risk of bias in this body of literature. Methods and findings We searched databases focused on biomedicine and global health for studies that estimated the effect of marrying before the age of 18 on any physical or mental health outcome or health behaviour. We identified 58 eligible articles, nearly all of which relied on cross-sectional data sources from sub-Saharan Africa or South Asia. The most studied health outcomes were indicators of fertility and fertility control, maternal health care, and intimate partner violence. All studies were at serious to critical risk of bias. Research consistently found that women who marry before the age of 18 begin having children at earlier ages and give birth to a larger number of children when compared to those who marry at 18 or later, but whether these outcomes were desired was not considered. Across studies, women who married as children were also consistently less likely to give birth in health care facilities or with assistance from skilled providers. Studies also uniformly concluded that child marriage increases the likelihood of experiencing physical violence from an intimate partner. However, research in many other domains, including use of contraception, unwanted pregnancy, and sexual violence came to divergent conclusions and challenge some common narratives regarding child marriage. Conclusions There are many reasons to be concerned about child marriage. However, evidence that child marriage causes the health outcomes described in this review is severely limited. There is more heterogeneity in the results of these studies than is often recognized. For these reasons, greater caution is warranted when discussing the potential impact of child marriage on health. We provide suggestions for avoiding common biases and improving the strength of the evidence on this subject. Trial registration The protocol of this systematic review was registered with PROSPERO (CRD42020182652) in May 2020.